The Effect of Using Flipbook and Kahoot in Increasing Students’ Reading Ability at the Second Grade of SMPN 33 Padang - Andreas, Mentari; Sari, Rosi Kumala; Suparmi; Dania, Rahma (Yayasan Citra Dharma Cindekia, 2024)
This study aims to address students' reading skill problems, such as lack of enthusiasm and interest in learning English reading, poor reading comprehension, and failure to achieve learning objectives and minimum literacy standards (KKM). To overcome these problems, this study used Kahoot and Flipbook as an intervention. This research was conducted at SMP N 33 Padang using one class as a sample selected through purposive sampling, namely class 8.7 with 32 students. The method used was pre-experimental with a single group design given a pretest and posttest. The pretest results showed that the average score of the experimental class was only 53.12, while after using Flipbook and Kahoot, the posttest results increased to 77.65. Data analysis using the t-test shows that the t-count value (14.737) is greater than the t-table (1.696), which means there is a significant difference between the pre-test and post-test scores of students' reading skills. This finding is supported by several previous studies which also show the effectiveness of using Flipbook and Kahoot in increasing students' interest, motivation, engagement, and comprehension in reading learning. Thus, it can be concluded that the use of Flipbook and Kahoot has a significant effect in improving the reading skills of second grade students of SMPN 33 Padang.